DRUG UTILIZATION REVIEW OF FLUOROQUINOLONES ANTIBIOTICS BY USING PRESCRIBING INDICATORS & COMPARISON OF DEFINE DAILY DOSE & PRESCRIBED DAILY DOSE IN OUTPATIENTS (International Journal of Pharmacy & Integrated Health Sciences, 2021)
Background: The increase in antibiotic resistance is new developing threat to healthcare system. Irrational drug use, polypharmacy and the current epidemic of bacterial resistance is attributed to the increase in use of antibiotics. The aim of the current study is to evaluate the difference between defined daily dose and prescribed daily dose of fluoroquinolones antibiotics.